A relative impact ranking of political studies In Ireland - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2009)
Against a background of the Irish government’s concerns with Key Performance Indicators (KPIs) and the British government’s wishes for a more quantitative Research Assessment Exercise (RAE), our study conducts a relative impact assessment of the study of politics, government, political science, and international relations in Ireland. Impact is measured as citations from the publications of permanent staff in eight Irish politics departments, based on data compiled in April 2008 from two leading academic indexes – ISI’s Web of Science and Scopus – as well as the now popular Google Scholar. We discuss some of the criticisms that naturally arise in a study of this nature. Then, following similar exercises in other disciplines (e.g. economics), we use the impact measures to compare and rank individual scholars as well as departments. We also explore the extent to which the choice of different indexes, and different measures, influences the results that we obtain. While there are differences, in particular between indexes based purely on articles and those that access books and other material, the results from the different indexes are strongly correlated.